Common hazards and their mitigating measures in work zones: A qualitative study of worker perceptions. (February 2015) - Debnath, Ashim Kumar; Blackman, Ross; Haworth, Narelle
Highlights: Roadworkers perceived speeding vehicles as the most common work zone hazard. Driver aggression towards roadworkers was commonly reported by traffic controllers. Working in wet weather, at night and close to traffic were the other notable hazards. Active police enforcement and improved driver education were perceived to be effective in improving work zone safety. Worker perceptions were found to be varied according to their exposure to hazards. Abstract: Road construction and maintenance activities present challenges for ensuring the safety of workers and the traveling public alike. Hazards in work zones are typically studied using historical crash records but the current study took a qualitative approach by interviewing 66 workers from various work zones in Queensland, Australia. This supplemented and enhanced the limited available data regarding the frequency and nature of work zone crashes in Australia, provided worker insights into contributing factors, and assessed their opinions on the likely effectiveness of current or future approaches to hazard mitigation. Workers may not be aware of objective data regarding effectiveness, but their attitudes and consequent levels of compliance can influence both the likelihood of implementation and the outcomes of safety measures. Despite the potential importance of worker perceptions, they have not been studied comprehensively to date, and thus this study fills a significant gap in the literature. Excessive vehicle speeds, driver distraction and aggression towards roadworkers, working in wet weather, at night and close to traffic stream were among the most common hazards noted by workers. The safety measures perceived to be most effective included police presence, active enforcement, and improving driver awareness and education about work zones. Worker perceptions differed according to their level of exposure to hazards.